Government Digital Communication Model in Corporate Social Responsibility Programs (Study in Gunung Kidul, Yogyakarta-Indonesia) - Fajri, Choirul; Najih, Muhammad; Longani, Kirti Dang; Novianto, Fiftin; Kusuma, Alan (Universitas Muhammadiyah Yogyakarta, 2024)
This research is a qualitative case study examining government digital communication in the implementation of Corporate Social Responsibility (CSR) programs in Gunung Kidul, Yogyakarta. Many companies have implemented CSR programs in Gunung Kidul, capitalizing on the area’s substantial tourism potential. However, the Regional Government, through the Regional Development Planning Agency (BAPPEDA), has yet to maximize its monitoring and evaluation of these programs, as it currently relies on conventional approaches. The purpose of this study is to identify a government digital communication model for CSR implementation, with a focus on the tourism sector. This model is developed from Werner’s concept of digital communication, incorporating cyberspace, virtual communities, interactivity, and multimedia. Few studies have explored a digital-based communication model for CSR; thus, this research aims to address that gap. By adopting this model, stakeholders can collaborate more effectively to enhance CSR efforts in Gunung Kidul’s tourism sector.